A QUANTITATIVE STUDY OF SCHOOL ADMINISTRATORS' WORK-LIFE BALANCE AND JOB SATISFACTION IN PUBLIC SCHOOLS - Karakose, Turgut; Kocabas, Ibrahim; Yesilyurt, Hayrullah (ISOSS PUBL, 2014)
The main purpose of this paper is to examine the level of school administrators' work-life balance and job satisfaction. In this context, the connection between school administrators' work-life balance and job satisfaction were investigated. In the present study, 139 school administrators were contacted, using a random sampling method. Descriptive statistics was used to identify participants' opinions in the study. Additionally regression analysis was utilized to establish whether work-life balance significantly predicts job satisfaction. According to the results obtained, it was seen that the levels of school administrators' job satisfaction were generally high level. At the same time it was determined that the balance of school administrators' work and family life was medium level. Finally, according to the result of regression analysis, a meaningful but low level correlation was established between school administrators' work-life balance and job satisfaction.
Keywords: Quantitative study; job satisfaction; school administrator; work-life balance; quality training; FAMILY CONFLICT; TEACHERS; Mathematics